The Pragmatics of Commitment - Kira Boulat (Peter Lang AG, Internationaler Verlag der Wissenschaften, 2023)
Commitment is connected to central linguistic features, such as modality and evidentiality. It has thus been investigated in many branches of the field. Building upon this heterogeneous literature, this book offers a cognitive pragmatic account of the processes involved in utterance interpretation, crucially when the hearer assesses the level of commitment linked to it. This research illustrates that the relevance-theoretic notion of strength can be used to capture the cognitive effects of commitment markers (as I think that X, I am sure that X, etc.). The author's model is based on a novel typology as well as predictions which were experimentally tested. The results show that commitment to an utterance is indeed cognitively determined by the strength of the hearer's corresponding assumptions.